Simulation of Energy Spectra of Protons from Solar Storm Event on January 27, 2012 - จันทร์นอก ชาญเรืองฤทธิ์ (KKU Science Journal, 2015)
We simulated numerically effects of shock acceleration of protons in the solar storm event of January 27, 2012, which was a strong level solar storm in the 24 th solar cycle. A model of finite time shock acceleration at the interplanetary medium was used in this study. We found that the simulation results agree well with the measurement of the energy spectra of protons from the PAMELA instrument onboard the Resurs-DK1 satellite.